IRON DEFICIENCY ANEMIA IN CHILDREN: EARLY DIAGNOSIS AND MODERN TREATMENT APPROACHES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This review explores current diagnostic and treatment strategies for iron deficiency anemia in children. It outlines the pathophysiology of the condition, highlights modern diagnostic tools, and evaluates therapies based on recent clinical trials and meta-analyses. Emphasis is placed on early detection using sensitive biomarkers, individualized iron supplementation, and preventive measures within pediatric care. The analysis supports the use of screening programs and advanced iron formulations to improve treatment outcomes. The review offers updated clinical guidance for healthcare professionals, stressing early intervention to prevent long-term developmental impacts